Synthesis and characterization of nickel zinc ferrite thin films deposited using spin coating technique - Yusuf, Yusnita (2016)
The trend for downsizing electronic devices and the potential applications of soft ferrite materials have leads to the fabrication of ferrite thin films. However, the main problem concerning the existing research is the fabrication of ferrite films, to make a simple technology at low temperature. Thus, in this work, we report some research findings on relationship of low annealing temperature towards morphological, magnetic and optical properties. Nickel zinc ferrite thin film was prepared via sol-gel and spin-coating technique. The films were coated with indium tin oxide (ITO) glass substrates and spin-coated. The samples were annealed from 400 °C to 700 °C using 100 °C increments with any one sample being subjected to only one annealing temperature. The structural and microstructural of Ni0.3Zn0.7Fe2O4 thin films were carried out by using X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). The M-H hysteresis loop of thin film was observed by using vibrating sample magnetometer (VSM). The formation of films and the vibration of molecules were also confirmed by using Fourier Transform Infrared (FTIR) spectroscopy. The XRD patterns showed an improvement of crystallinity with increasing annealing temperature. Plane (311) most intense plane formed nickel zinc ferrite phases. The spinel structure was also confirmed by FTIR. FESEM image showed films have dense and homogenous grains with average grain size are 18.61 nm (400 °C), 26.25 nm (500 °C), 28.12 nm (600 °C) and 41.32 nm (700 °C). The measured resistivity was found to increase with increasing temperature, however decreased after annealed at 700 °C due to the combined effect of increased grain size and Fe2+ ions due to increasing zinc loss. The synthesized of Ni0.3Zn0.7Fe2O4 ferrite thin films showed narrow with a low saturation magnetization (Ms). The value of Ms are 1.28, 2.39, 2.65 and 3.42 emu/g respectively. These attributed to the presence of small nanoparticles containing a spin-glass-like surface layer and ferrimagnetically lined-up core spins. The coercivity is decreases as increase the average grain size, 16.18, 16.54, 12.28, and 8.30 Oe respectively. The highest of energy bandgap obtained for direct and indirect bandgap 3.57 and 3.30 eV.